O mistyce i filozofii Mistrza Eckharta oraz jej funkcjach pedagogicznych = On the mysticism and philosophy of master Eckhard and their applications in pedagogy - Palewski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The dissertation demonstrates Eckhard's philosophy and mysticism and pedagogical applications of his works.
Keywords: Hochheim, Eckhart von (filozof, mistyk; ok. 1260-ok.1327/1328); filozofia niemiecka